2021
DOI: 10.1155/2021/9991175
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA H19/miR-766-3p/S1PR3 Axis Contributes to the Hyperproliferation of Keratinocytes and Skin Inflammation in Psoriasis via the AKT/mTOR Pathway

Abstract: Background. The pathogenesis of long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) are well studied in psoriasis. However, little is known about how specific lncRNAs and miRNAs affect the mechanism of psoriasis development and which pathways are involved. Objectives. To explore the role of the lncRNA H19/miR-766-3p/S1PR3 axis in psoriasis. Methods. miRNA and lncRNA microarrays were performed using IL-22-induced HaCaT cells and psoriatic lesions, respectively. Fluorescence in situ hybridization and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…This study identified a potential downstream miRNA (miR-766) of circPTK2 and found that miR-766 was down-expressed in both models of septic ALI, but circPTK2 depletion restored miR-766 levels. miR-766 has been recognized to suppress skin inflammation 35 and attenuate ischemia/perfusion injury-induced cellular inflammation and apoptosis 36 . The paper demonstrated that miR-766 overexpression mitigated the effects of circPTK2 overexpression on cytotoxicity, eATP levels, inflammation, and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified a potential downstream miRNA (miR-766) of circPTK2 and found that miR-766 was down-expressed in both models of septic ALI, but circPTK2 depletion restored miR-766 levels. miR-766 has been recognized to suppress skin inflammation 35 and attenuate ischemia/perfusion injury-induced cellular inflammation and apoptosis 36 . The paper demonstrated that miR-766 overexpression mitigated the effects of circPTK2 overexpression on cytotoxicity, eATP levels, inflammation, and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“… [ 49 ] LINC00941 Down keratinocyte Inhibits early keratinocytes differentiation [ 50 ] H19 Down Skin As a sponge for miR−766-3p, upregulates S1PR3 levels and regulates psoriatic keratinocyte proliferation and skin inflammation via the AKT/mTOR pathway. [ 51 ] MEG3 Down Skin/HaCaT Blocked regulation of inflammation and autophagy in keratinocytes by TNF-α through the PI3K/AKT/mTOR signaling pathway. [ 52 ] LncRNA-AL162231.4 Down Skin - [ 35 ] ST7OT Down Skin - [ 33 ] LOC285194 Down Skin - [ 33 ] Car Intergenic 10 Down Skin - [ 33 ] NONHSAT044111 Down Skin - [ 48 ] Note: nuclear factor-κB (NF-κB); interleukin enhancer binding factor 2 (ILF2); signal transducer and activator of transcription (STAT); Janus kinase (JAK); extracellular regulated kinase (ERK); AKT serine/threonine kinase 1 (AKT); mechanistic target of rapamycin (mTOR); competitive endogenous RNA (ceRNA); Phosphoinositide 3-kinase (PI3K); Sphingosine 1-phosphate receptor 3 (S1PR3).…”
Section: Lncrnas and Psoriasismentioning
confidence: 99%
“…Furthermore, S1PR2 expression is upregulated in Staphylococcus-aureus-stimulated keratinocytes, and S1PR2 is involved in the formation of skin barrier structures, such as filaggrin, claudin, occludin, and corneodesmosin [ 13 , 14 ]. Moreover, S1PR3 has recently been reported to contribute to the upregulation of IL-17A and IL-22 secretion via the AKT/mTOR pathway [ 53 ] ( Figure 3 ).…”
Section: S1p and S1p-s1pr Pathways On Human Keratinocytesmentioning
confidence: 99%
“…S1PR3 is also related to the mechanism of psoriasis. He et al [ 53 ] reported S1PR3 axis contributes to the hyperproliferation of keratinocytes and skin inflammation in psoriasis via the AKT/mTOR pathway. For S1PR4, Schuster et al [ 72 ] reported that imiquimod-induced psoriatic skin lesions created in S1pr4-deficient mice reduce the severity of psoriasiform dermatitis, decrease CCL2, IL-6, and CXCL1, and reduce infiltrating monocytes and granulocytes.…”
Section: S1p-s1pr Signaling and Skin Diseasesmentioning
confidence: 99%